A regioquímica das reações de Diels-Alder de N-tosil para-benzoquinona iminas - Uliana, Marciana Pierina (2012)
In this work it was done a comparative study on the reactivity of a variety of dienophiles including para-benzoquinones, their mono-oximes, their N-tosyl mono-oximes and their N-tosylimines on the Diels-Alder reactions with simple dienes. The synthesis of the dienophiles was performed through chemical modifications from the corresponding phenols as represented in Scheme I. The studies of the reactivity of these dienophiles in the Diels-Alder reactions with cyclopentadiene were the first to be conducted and furnished the corresponding cycloadducts as shown in the Scheme II. The reactivity of the N-tosylimines para-benzoquinones were tested on the Diels-Alder reactions with of the dienes 2,3-dimethyl-1,3-butadiene and 2-methyl- 1,3-butadiene (isoprene) (Scheme III). Concomitant to the experimental study on the reactivity of the dienophiles, it was done a study of theoretical calculations where was obtained the differences between the energies of the HOMO orbital of the cyclopentadiene and LUMO orbitals of the dienophiles confirming their reactivity. These calculations were performed using the DFT calculation using the basis set B3LYP/6-31 + G (d,p) and furnished the energies of the transition states of the cycloadducts. It was also possible to predict which cycloaddition product would be mainly formed and to determine what are the kinetic and thermodynamic products. Tests of the biological activity of the dienophiles were conducted in collaboration with Professor Dr: Damião P. de Sousa from UFSE.